PENINGKATAN IMUNITAS MELALUI GIZI SEIMBANG TINGGI ANTIOKSIDAN PADA ODHA DI WILAYAH BLITAR RAYA - winarni, sri; Martiningsih, Wiwin; Mustafa, Annasari (Politeknik Kesehatan Kemenkes malang, 2023)
The HIV virus progressively weakens the immune system, and causes malnutrition, weight loss and muscle wasting. This is due to increased body metabolism but decreased intake, sometimes accompanied by nausea, vomiting and decreased appetite due to the drugs given, accompanied by with diarrhea for more than two weeks, as well as mouth ulcers due to fungal infections and difficulty swallowing. Based on 2021 data, there are 49 people living with HIV in the city of Blitar and the data available at health facilities is very supportive, namely that the average CD4 cell examination of PLWHA has decreased. This problem needs to be addressed immediately, because it hampers the goals of HIV AIDS management, especially the fast track 95-95-95 program, which means 95% of PLWHA know their HIV status, 95% of PLWHA take ARVs, and 95% of PLWHA have suppressed viral loads. This community service activity aims to increase the immunity of PLWHA in the greater Blitar area through consuming balanced nutrition & high in antioxidants. The target is 25 PLWHA who are actively participating in Peer Support (KDS) groups in Blitar Raya. Normal CD4 test results are 500 to 1,600 cells per mm3 of blood (cells/mm3). Of the 25 PLWHA, 18 people (72%) had a score below (500) and 7 people (28%) had a score above (500), with the lowest score being 81 and the highest result being 959. In general, they had good motivation and were taking ARV medication. routinely. The activity continued with education about how to eat healthy food properly, how to choose food ingredients high in anti-oxidants, how to cook it properly, and also taught how to practice food portioning for PLWHA